Rectovaginal fistula with anal atresia in 5 dogs - Rahal, Sheila Canevese [UNESP]; Vicente, Cristiane S. [UNESP]; Mortari, Ana C. [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Caporalli, Evelyn H.G. [UNESP] (My University, 2007)
Five dogs with rectovaginal fistula and atresia ani that had been treated by surgical correction of the malformations were studied retrospectively. Ages at presentation varied from 1 to 3 months and weight from 350 g to 7.5 kg. The histories included voiding of feces through the vulva, with or without tenesmus, usually observed after weaning. Artesia ani, presence of feces in the vaginal canal, abdominal distention, and discomfort on abdominal palpation were observed during clinical examination. Also, 3 dogs had partial tail agenesis. In all dogs, the rectovaginal fistula was isolated and transected, the vulvar and rectal defects were closed separately, and the atresia ani was repaired. Normal defecation was restored, but 1 dog had fecal incontinence that subsequently resolved. One dog died 2.5 months postoperatively, and follow-up was done on the others for periods ranging from 1.6 year to 7.7 years. Surgical correction in dogs with rectovaginal fistula and atresia ani may result in a favorable outcome, if it is done early.
Keywords: animal; animal disease; anus atresia; defecation; dog; dog disease; feces incontinence; female; physiology; rectovaginal fistula; retrospective study; time; treatment outcome; Animals; Anus, Imperforate; Defecation; Dog Diseases; Dogs; Fecal Incontinence; Female; Rectovaginal Fistula; Retrospective Studies; Time Factors; Treatment Outcome; Canis familiaris; Fistula